Reciprocal changes in maternal and fetal metabolism of corticosterone in rat during gestation - Vagnerová, K; Vacková, Z; Klusonová, P; Staud, F; Kopecký, M; Ergang, P; Miksík, I; Pácha, J (Reproductive sciences (Thousand Oaks, Calif.), 2008)
OBJECTIVE: The objective of this study was to investigate the role of 11beta-hydroxysteroid dehydrogenases (11HSD1 and 11HSD2) in determining the fetal concentration of glucocorticoids. METHODS: The expression patterns for mRNA abundance, protein level, and enzyme activities of placental and fetal 11HSD1 and 11HSD2 were assessed from embryonic day 13 (E13) to day 21 (E21; term E22). The transplacental passage of maternal corticosterone and its contribution to fetal glucocorticoids was also studied. RESULTS: Placental 11HSD1 mRNA decreased between days E13 and E14 and then remained at much lower values up to E21. Similarly, NADP+-dependent 11beta-oxidation and 11-reduction were lower in late gestation. In contrast, placental 11HSD2 mRNA and protein decreased between E13 and E21. Dithiothreitol increased the activity of 11HSD2 and the output of 11-dehydrocorticosterone into fetal circulation.The fetal activity of 11HSD1 increased and 11HSD2 decreased between E16 and E21. CONCLUSIONS: The final third of gestation is accompanied by reciprocal changes in placental and fetal metabolism of corticosterone due to changes in 11HSD1 and 11HSD2 not only at the level of transcription but also at a posttranslational level.
Keywords: kortikosteron; techniky in vitro; Pregnancy; Placenta; Female; 11-beta-hydroxysteroiddehydrogenasa typ 1; Corticosterone; krysa rodu Rattus; 11-beta-Hydroxysteroid Dehydrogenase Type 2; zvířata; potkani Wistar; Fetus; plod; těhotenství u zvířat; 11-beta-Hydroxysteroid Dehydrogenase Type 1; ženské pohlaví; Rats, Wistar; 11-beta-hydroxysteroiddehydrogenasa typ 2; těhotenství; In Vitro Techniques; Rats; Pregnancy, Animal; Animals; placenta